2022
DOI: 10.9734/jpri/2022/v34i35b36172
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age, Gender and Type of Diabetes with Thiamine Level: A Cross-Sectional Analysis

Abstract: Objective: Diabetes Mellitus has been observed to be related with low thiamine levels in the body, as it affects directly on carbohydrate metabolism. Therefore, this study was intended to assessdemographic characteristics and serum thiamine levels in type I and type II diabetic patients and healthy control group. Methodology: This was a case-control study carried out in diabetic outpatient department (OPD) of Urban Health Center and New Karachi, Hospital. The duration of the study was about six months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…One study revealed that people with type 1 DM had considerably lower serum thiamine levels than those with type 2 DM and healthy controls [ 16 ]. Thiamine levels in patients with type 1 DM were significantly lower than those in controls in a previous study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that people with type 1 DM had considerably lower serum thiamine levels than those with type 2 DM and healthy controls [ 16 ]. Thiamine levels in patients with type 1 DM were significantly lower than those in controls in a previous study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%